2019
DOI: 10.1007/s11926-019-0819-8
|View full text |Cite
|
Sign up to set email alerts
|

The European Map of Axial Spondyloarthritis: Capturing the Patient Perspective—an Analysis of 2846 Patients Across 13 Countries

Abstract: Purpose of Review Scientific research in axial spondyloarthritis (axSpA) has grown significantly. Nevertheless, the patient perspective remains insufficiently explored. Using a cross-sectional survey, the European Map of Axial Spondyloarthritis (EMAS) describes how patients living with self-reported axSpA experience their disease physically, psychologically, and socially. Recent Findings 2846 patients participated: mean age 43.9 ± 12.3 years, 61.3% female, mean disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 19 publications
(19 reference statements)
5
87
0
1
Order By: Relevance
“…Despite advances in our understanding of axSpA and improved education initiatives for HCPs, a recent survey of 2846 patients across 13 countries reported that the mean diagnostic delay has remained in the region of ∼8 years [ 38 ]. While an additional UK study published in 2015 found a stable mean diagnostic delay of 8–9 years and a median delay of 5 years prior to and after the 2009 updated classification criteria [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in our understanding of axSpA and improved education initiatives for HCPs, a recent survey of 2846 patients across 13 countries reported that the mean diagnostic delay has remained in the region of ∼8 years [ 38 ]. While an additional UK study published in 2015 found a stable mean diagnostic delay of 8–9 years and a median delay of 5 years prior to and after the 2009 updated classification criteria [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is often a substantial delay between symptom onset and axSpA diagnosis, with recent reports suggesting an average diagnostic delay of 5-14 years [6][7][8][9][10][11]. One factor contributing to the delay in diagnosis of axSpA is the difficulty in distinguishing inflammatory back pain (IBP), a key symptom of axSpA that affects the spine and sacroiliac joints [12,13], from other highly prevalent forms of low back pain in the general population-the overall global prevalence of low back pain is approximately 9% [14], and up to 80% of adults will experience low back pain in their lifetime [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…(1) The studies were published open epidemiological studies on AS in mainland China. (2) The study subjects were recruited by sampling methods or from a healthy population in a certain region, with clear and detailed sample numbers, numbers of cases or prevalence rates. Relevant data were extracted directly from the literature or calculated with original data.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…(1) The studies were republications or duplicate studies. (2) The study data contained obvious errors or were incomplete or unclear and relevant data could not be obtained by contacting the authors. (3) The study sample sources were those who suffered from confirmed AS, had not been diagnosed but had a high possibility of AS, or had a family history of AS.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation